(untitled) (Journal of Tourism and Himalayan Adventures, 2020)
The paper focuses on religious aspect of Aaryaghat situated on the banks of holy river Bagmati within the periphery and premises of Pashupatinath temple. Hindus believe that if the dead person gets the funeral and rituals performed here then the gateway to heaven opens. This final journey is taken as the last walk to Aaryaghat and is done with a symbolic religious belief. The Aaryaghat of Pashupatinath area is a very sacred place where Hindus’ cremation process is performed for the purification of the dead and the departed soul. The rituals are related to the Hindu belief of salvation, rebirth and attainment of heaven. After the death, there are various ritual practices to be done like Sharadha annually and such rituals are performed by the kin folks devoutly on the belief of attaining a heavenly place in the realms of trinity Gods. The paper has only focused on the aspect of the last walk concept and the Aaryaghat at the Pashupatinath through personal observation and secondary literature review.